Pemberdayaan Ekonomi Masyarakat Desa Melalui Pembudidayaan Jamur Tiram - Sabana, Moh. Bahrulloh; Fu'in, Hilwa Saida; Nashihah, Risalatun; Wibakti, Aji Restu; K. P, Desy Edkhonanda; Ayu, Yamita; Nurvaniati, Ikke Aprilia; Wajdi, Muh Barid Nizarudin (Bisma : Bimbingan Swadaya Masyarakat, 2023)
the engagement is aimed to increasing people's income, especially during the pandemic. The object of assistance is the cultivation of oyster mushrooms in Garu Village. The method used is ABCD to map the potential in Garu Village. The results of mentoring show that there needs to be an improvement in the quality of oyster mushroom cultivation, especially in production and marketing.